Developing a digital field notebook for bioscience students in higher education - Maddison, Janine; Bevan, Richard Martin; Marsham, Sara (Frontiers in Education, 2023)
The use of mobile device presents both benefits and barriers. However, studies into the use of technology in fieldwork often focus only on either practitioner views or student views. Digital field notebooks (DFNs) are one-way mobile devices can be used to enhance fieldwork. Yet their use is limited to Geography, Earth and Environmental Science (GEES) disciplines, with students often playing a passive role during the development of DFNs. This research reports on the development of a DFN to enhance bioscience fieldwork in Higher Education (HE). Using interviews, focus groups, and survey methods we investigated how both fieldwork practitioners and learners view the role of technology in the field. Working in partnership with students, we explored their experiences of using a DFN during fieldwork. Feedback was utilised to make changes to the DFN to support its integration within bioscience fieldwork.Overall, valuable developments related to content, technology, and pedagogy were made to the DFN, identifying value in a co-creation process. For example, students suggested the role of the DFN as a collaborative tool where individual entries were collated together. A workflow schematic and case study are presented for how a DFN can be used during bioscience fieldwork in HE.Although students identified place connection and the development of reflective practice as particular affordances, students did not identify any digital skill development opportunities when using the DFN. Additionally, although students suggested the DFN was easy to use, barriers remain for students in using a DFN.We suggest further research on the complex issues of permission and perceptions of value of mobile device use during fieldwork. Additionally, more explicit reference to digital skill developments should be made when using a DFN.